2017
DOI: 10.1002/cav.1745
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual evaluation of synthetic gaze jitter

Abstract: Eye movements are an essential part of non‐verbal behavior. Non‐player characters, as they occur in many games, communicate with the player through dialogue and non‐verbal behavior and can have a strong influence on player experience or even on gameplay. In this paper, we evaluate a procedural model designed to synthesize the subtleties of eye motion. More specifically, our model adds microsaccadic jitter and pupil unrest both modeled by 1/fα or pink noise to the saccadic main sequence. In a series of perceptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Pink noise has been widely used to model biological motions. 45 Duchowski et al 45 and Krejtz et al 13 found that it can be used to model the subtle changes in pupil size. A similar result was found by Jörg et al 46 showing that adding pink noise to the pupil size and eyeball motions of different virtual characters created animations with similar perceived naturalness than a motion captured approach and perceived as significantly more natural than animations with only keyframed eyeball motions and pupil size changes without pink noise.…”
Section: Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pink noise has been widely used to model biological motions. 45 Duchowski et al 45 and Krejtz et al 13 found that it can be used to model the subtle changes in pupil size. A similar result was found by Jörg et al 46 showing that adding pink noise to the pupil size and eyeball motions of different virtual characters created animations with similar perceived naturalness than a motion captured approach and perceived as significantly more natural than animations with only keyframed eyeball motions and pupil size changes without pink noise.…”
Section: Descriptionmentioning
confidence: 99%
“…Previous research has focused on making the dynamics of the eyeball realistic, 9 as well as the motions of the eyelids. 10,11 With advances in eye tracking, there is now work on adding subtle pupil dynamics, such as pupil jitter 12,13 and pupil light reflex. 14 While this past research has performed perceptual studies to show that adding realistic dynamics to the eyeballs, eyelids, and pupils improves the perceived realism and naturalness of a virtual avatar, there has been little investigation into how cues in the eyes impact the perceived internal state of a virtual avatar.…”
Section: Introductionmentioning
confidence: 99%